2021
DOI: 10.1142/s2737416521500356
|View full text |Cite
|
Sign up to set email alerts
|

AnIn-SilicoApproach to Evaluate the Inhibitory Potency of Selected Hydroxamic Acid Derivatives on Zinc-Dependent Histone Deacetylase Enzyme

Abstract: Histone deacetylase (HDAC) enzymes modify the histone by removing the acetyl group from the lysine residues, known as histone deacetylation. HDACs have been involved in altering gene expressions, resulting in cancer cells in the body. This study focuses on HDAC inhibitors’ impact on histone deacetylase-like protein (HDLP) stability through computational techniques. Molecular dynamics (MD) analyses were used to examine the atomic-level description of drug binding sites and how the HDAC inhibitors change the HDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The result showed that the stability of HDLP–CBHA (m-Carboxycinnamic acid bis-hydroxide (CBHA)) is higher than that of the free HDLP enzyme. The higher stability was contributed by the increased number of hydrogen bonds [ 15 ]. Similarly, computational modeling of a prospective drug, dorzagliatin, showed it interacting with human glucokinase activator (GKA).…”
Section: Electrostatics Of Wild-type Biological Macromoleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…The result showed that the stability of HDLP–CBHA (m-Carboxycinnamic acid bis-hydroxide (CBHA)) is higher than that of the free HDLP enzyme. The higher stability was contributed by the increased number of hydrogen bonds [ 15 ]. Similarly, computational modeling of a prospective drug, dorzagliatin, showed it interacting with human glucokinase activator (GKA).…”
Section: Electrostatics Of Wild-type Biological Macromoleculesmentioning
confidence: 99%
“…Molecular dynamics and MMPBSA methods were also used to probe the effect of inhibitors. This was done in the case of histone deacetylase-like proteins, and showed that affinity increases with the increase in hydrogen bonds [ 15 ]. Similarly, inhibitors against cyclin G-associated kinase involved in hepatitis C virus entry into host cells were studied, and short-range interactions were analyzed [ 34 ].…”
Section: In Silico Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…The acetylation of lysine residues found in the N terminal of core histone is one of the post-translational chromatin modifications that affect gene expression [6]. Acetylation and deacetylation of histones are restricted by the enzymes of histone acetyltransferase and histone deacetylase (HDACs) [7]. Alterations of gene expression are a hallmark of cancer, and evidence suggests an epigenetic mechanism mediates at fewest a component of these alterations [8].…”
Section: ■ Introductionmentioning
confidence: 99%